A natação como auxiliar no desenvolvimento escolar de alunos com Transtorno do Espectro Autista (TEA) - Noviscki, Juliane [UNESP] (2017)
With changes in the autism nomenclature, the most current term is Autism Spectrum Disorder (ASD), which has clinical characteristics of isolation, with extreme difficulty in establishing links with people or situations, absence of language, refusal of food, sudden movements, repetition of attitudes and manipulation of objects. There is no exam to diagnose the cause; the child neurologist, along with other professionals, identifies the diagnosis. Every child has the right to education in the regular school system, with the expansion of inclusive education teachers are seeking training to meet the demand, and physical education is a link of great importance in this inclusion, since adequate physical activity the possibilities of the subject, values, integrates with reality, obtaining autonomy, self-confidence and freedom. Swimming as an extracurricular activity helps in the development of these children, since water is the facilitating medium, which provokes challenges and allows the child free and independent movements, as well as the playful actions that stimulate the expansion of social interaction, contributing to the organization affective and psychomotor partner of the child. The objective of the study was to identify the behavioral changes in the school of the child with ASD during the participation of a swimming practice program. The results showed that there was an improvement in the behavior, and they emphasized the question of following rules, the responsibility of the students during the classes in the school, as well as the improved socialization, since the child with ASD presented less tense and more motivated in the school, which facilitated their learning